A Caravana do Cordel e a construção de um Nordeste em movimento em São Paulo - Geribello, Francisca Batista Barbosa (2013)
The Caravana do Cordel and the building of a northeast in movement in São Paulo is a research about the way the stories are mobilized, the actions and representations of the Northeast of Brazil in the speeches of Northeastern migrants settled in São Paulo, belonging to the Caravana do Cordel . I investigate the reinterpretation that is built by those subjects who maintain a strong mnemonic relationship with the Northeast of Brazil, with the lived experiences in this geographical space, social and symbolic, both in the past and present. I assume that although these poets crystallize a certain image of the Northeast of Brazil where they were born, they also create other northeastern", through a discursive dynamic construction.